DESAIN AIRFOIL MENGGUNAKAN SOFTWARE CAEDIUM - Mangestiyono, Wiji (Gema Teknologi, 2012)
Wiji Mangestiyono, in paper airfoil design use caedium software explain that caedium and its add-ons combine to form an easy-to-use Computational Fluid Dynamics (CFD) software system that can help to assess the performance of Â 3D model. Using Caedium add-ons can create any 2D or 3D geometry or import geometry from another CAD package. Then simulate how a gas (e.g. air) or liquid (e.g. water) will flow over and through Â geometry. Caedium is simple to learn and efficient to use. Every body can study how the physics of its model changes over time or as modify the model in real time. Caedium's unified simulation environment makes it easy to change the model on the fly and quickly see the results of the changes. Keywords : Caedium, Airfoil, Computation Fluid Dynamics